Ultrasound assisted extraction of bioactive compounds from BRS Violet grape pomace followed by alginate-Ca2+ encapsulation. (15th February 2021) - Bruno Romanini, Edilson; Misturini Rodrigues, Leticia; Finger, Aline; Perez Cantuaria Chierrito, Talita; Regina da Silva Scapim, Monica; Scaramal Madrona, Grasiele
Highlights: Ultrasound increase the extraction of phenolic compounds from grape pomace. The peel of the hybrid cultivar BRS Violet is high polyphenol content. Cyanidin chloride was identified for the first time in the BRS Violet grape variety. Alginate was used as an encapsulating agent for grape skin phenolic compounds. Half-life of the grape alginate-Ca 2+ capsules is higher in the light absence. Abstract: Objective of this study was to recover bioactive compounds from grape pomace, and to investigate the effect of thermosonication in the rate of aqueous extraction. The best extraction for phenolics and total anthocyanins, was at 55 °C, amplitude of 40% and 6 min of treatment. The ultrasound assisted extraction showed superior results when compared to conventional extraction, extraction averages were: 11% total phenolic compounds, 25% total anthocyanins. The extract obtained by ultrasound showed higher antioxidant capacity when compared to the one obtained by conventional extraction. The alginate-Ca 2+ capsules were stable when stored in the presence or absence of light, with a reduced t1/2 (absence of light), indicating longer half-life in the absence of light. The use of thermosonication favored greater amounts of bioactive compounds in the grape pomace aqueous extract, and this encapsulated extract in alginate-Ca 2+ shows good stability and less degradation in the light absence.